Breakfast Behavior and Limited Types of Food influence the nutritional status of working mothers Informal Sector in Sungai Ambawang, Kubu Raya - Pujana, Betri; Widyastutik, Otik; Trisnawati , Elly (Sean Institute, 2022)
Nutritional status is the condition of the body due to food consumption which achieves success in fulfilling nutrition and a balance between the amount of nutrient intake and the amount needed by the body. The number of female workers in Indonesia tends to increase from year to year, but the health and nutritional status of workers in general has not received attention. Research objectives this for knowing connection Knowledge, Breakfast Behavior, Limited Types of food with nutritional status Mother work in the informal sector. Research type this is using a cross sectional design. Number of Samples in study this is as many as 51 working mothers Informal sector, taking sample in study this using purposive sampling, data analysis techniques using the Chi-Square test. Research results there is connection significant Among Breakfast Behavior (p=0.015) and Limitations type food (p=0.033), nutritional status Mother work informal sector, and no there is connection between, Knowledge (0.986) with nutritional status Mother work informal sector.